Asthma and exercise induces bronchospansm - Fischetto, G. (New Studies in Athletics, 2010)
Exercise induced asthma or bronchospasm (EIA or EIB) is a transient, reversible, and intermittent narrowing of the airways, occurring about 10-15 minutes after intense exercise (aerobic activity more than anaerobic), performed for 8-10 minutes. It affects up to 18% of the general population, depending on reporting methodology, and its documented prevalence among athletes is up to 20%. Many treatments are available, starting with education and prevention, to enable avoidance of possible trigger factors and reduce the exacerbation of symptoms. Pharmacologic agents are useful both for prevention and treatment, even if their use should always be adapted to the individual conditions. For athletes, special care must be taken to integrate any treatment option with the training and competition programme, particularly with regard to anti-doping regulations. IAAF and WADA rules oblige athletes to obtain a diagnosis and/or a therapeutic use exemption before use of some medicines included in the WADA lists of banned substances and methods. This artide presents an over-view of the current literature on asthma, its treatment and implications for athletes. The aim is to give information and guidance to athletes, their coaches and particularly their medical support.